(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, aspects specific to Iqbal Mirzo’s poetry were drawn into analysis using the example of his lyrical works. In the poet’s Poems, the expression of the problems of subject and Idea, person and period in harmony with the experiences of the lyrical hero was examined through such research methods as psychological, structural-poetic, descriptive. The aesthetic sources of Iqbal Mirzo’s work have been studied on the basis of poetic examples in which Alisher was manifested through creative influence from the image style characteristic of Navoi’s work, achieving an impressive expression of thought through the use of classical poetic arts.